Developmental Associations between Short-Term Variability and Long-Term Changes: Intraindividual Correlation of Positive and Negative Affect in Daily Life and Cognitive Aging - Hülür, Gizem (Dev Psychol, 2015)
Conceptual notions and empirical evidence suggest that the intraindividual correlation (iCorr) of positive affect (PA) and negative affect (NA) is a meaningful characteristic of affective functioning. PA and NA are typically negatively correlated within-person. Previous research has found that the iCorr of PA and NA is relatively stable over time within individuals, that it differs across individuals, and that a less negative iCorr is associated with better resilience and less vulnerability. However, little is known about how the iCorr of PA and NA relates to cognitive aging. This project examined how the association between PA and NA in everyday life is associated with long-term cognitive aging trajectories. To do so, we linked micro-longitudinal data on PA and NA obtained on up to 33 occasions over six consecutive days with macro-longitudinal data on fluid and crystallized cognitive abilities obtained over 15 years from a subsample of Berlin Aging Study participants (N = 81, mean age at the micro-longitudinal study = 81 years, range 73–98; 41% women). Over and above age, gender, education, overall levels of PA and NA, and number of health conditions, a less negative iCorr of PA and NA was associated with lower levels of cognitive ability and steeper cognitive declines, particularly for fluency and knowledge abilities. We discuss possible mechanisms for this finding and argue that a less negative iCorr of PA and NA may be indicative of deficits in emotional integration that are tied to changes in crystallized aspects of cognitive abilities.